2017
DOI: 10.4236/ijmpcero.2017.64041
|View full text |Cite
|
Sign up to set email alerts
|

A Post-Mastectomy Radiation Therapy Dose Distribution Study

Abstract: Purpose: For post-mastectomy radiation therapy, skin dose must be accurately estimated to assess skin reactions, such as: erythema, desquamation, and necrosis. Even with advanced algorithms, planning systems do not always provide accurate dosimetry for target volumes distal to skin. Methods and Materials: In this study, a female anthropomorphic (ART) phantom and the newest generation of optically stimulated luminescence dosimeters (OSLD) (nanoDots, Landauer Inc.) were deployed to measure chest wall dose distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several authors have compared TPS calculated surface dose with measured dose and have reported overestimation as well as underestimation of the surface dose by OSLD. [232425] One reason for the variations in estimation is that the measurements were done at the build-up region where the change of a few mm of depth may result in a significant change in dose. Second, OSLD which has a WED of 0.4 mm overestimates the surface dose when compared to detectors which have a lower WED. Positional errors in the placement of OSLD during measurement may also contribute to the variation between TPS calculated dose and measured dose.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have compared TPS calculated surface dose with measured dose and have reported overestimation as well as underestimation of the surface dose by OSLD. [232425] One reason for the variations in estimation is that the measurements were done at the build-up region where the change of a few mm of depth may result in a significant change in dose. Second, OSLD which has a WED of 0.4 mm overestimates the surface dose when compared to detectors which have a lower WED. Positional errors in the placement of OSLD during measurement may also contribute to the variation between TPS calculated dose and measured dose.…”
Section: Resultsmentioning
confidence: 99%